The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.jmedchem.0c02039
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Proteome-Wide Scale Screening for the 5-Alpha Reductase Inhibitor Finasteride: Identification of a Novel Off-Target

Abstract: Finasteride, a 5-alpha reductase (5α-R) inhibitor, is a widely used drug for treating androgen-dependent conditions. However, its use is associated with sexual, psychological, and physical complaints, suggesting that other mechanisms, in addition to 5α-R inhibition, may be involved. Here, a multidisciplinary approach has been used to identify potential finasteride off-target proteins. SPILLO-PBSS software suggests an additional inhibitory activity of finasteride on phenylethanolamine N -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 91 publications
1
12
0
1
Order By: Relevance
“…It may be expected that the presence of MV1035 makes it difficult for the methylated nucleobase within DNA to reach the right site for the enzymatic reaction ( Figure 2 C,D). Noteworthy, the PBS for MV1035 within ALKBH2 was identified despite being partially closed and apparently inaccessible to the ligand (see Supplementary Figure S1 and Supplementary Table S2 ) thanks to SPILLO-PBSS’s ability to take into account protein flexibility [ 16 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…It may be expected that the presence of MV1035 makes it difficult for the methylated nucleobase within DNA to reach the right site for the enzymatic reaction ( Figure 2 C,D). Noteworthy, the PBS for MV1035 within ALKBH2 was identified despite being partially closed and apparently inaccessible to the ligand (see Supplementary Figure S1 and Supplementary Table S2 ) thanks to SPILLO-PBSS’s ability to take into account protein flexibility [ 16 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Giatti et al identified an off-target effect of finasteride on phenylethanolamine N-methyltransferase (PNMT), a limiting enzyme for the production of epinephrine (EPI) from norepinephrine. 105 Catecholamines including EPI have been found…”
Section: Androgen Mediation Of Angiogenesismentioning
confidence: 99%
“…Importantly, some of these effects of finasteride persisted even one month after withdrawal [ 51 ]. Furthermore, recent studies show finasteride exerts inhibitory effects on the rate-limiting enzyme responsible for adrenaline production, complicating its use in stress-related studies [ 52 ]. Given the role of sex steroids in the organisation of the HPA axis during the perinatal period and puberty [ 53 ], the use of finasteride during pregnancy or sensitive postnatal developmental windows may lead to sex-specific side-effects; hence, outcomes should be considered with this caveat in mind.…”
Section: Role Of Neurosteroids In Programming During the Critical Dev...mentioning
confidence: 99%